Local application of tetracycline solution with a microbrush: An alternative treatment for persistent periodontitis - Bosco, Joseane M.D. [UNESP]; Lopes, Beatriz M.V. [UNESP]; Bosco, Alvaro F. [UNESP]; Spolidorio, Denise M.P. [UNESP]; Marcantonio, Rosemary A.C. [UNESP] (My University, 2009)
Objective: Topical antibiotics may overcome shortcomings of mechanical therapy for localized persistent periodontitis. This double-center, single-blind, randomized controlled study aimed to evaluate the microbiologic profile and clinical parameters of persistent periodontal pockets after treatment with tetracycline solution. Method and Materials: Thirty-seven patients who had at least 4 nonadjacent sites of persistent periodontal pockets with probing depth of at least 5 mm and bleeding on probing were randomly assigned to test and control groups. In the test group, 2 teeth received 4 applications of tetracycline solution (100 mg/mL) with a microbrush (T), while the other 2 teeth received the same treatment plus 1 session of scaling and root planing (SRP+T). In the control group, 2 teeth received 1 session of scaling and root planing (SRP), and the other 2 teeth received 4 applications of saline with a microbrush plus 1 session of scaling and root planing (SRP+S). Clinical parameters of probing depth, bleeding on probing, visible plaque index, gingival bleeding index, gingival recession, as well as clinical attachment level and subgingival plaque samples (evaluated by polymerase chain reaction) were measured at baseline and 1, 3, and 6 months. Results: All therapies yielded statistically significant data on clinical measurements with no significant differences among groups. Presence of bacteria decreased in both groups, but only in the test group was a significant decrease of Porphyromonas gingivalis, Tannerella forsythia, and Actinobacillus actinomycetemcomitans noted up to 6 months. Conclusion: Tetracycline applied with a microbrush may be an alternative treatment for persistent periodontitis that can probably be mediated by reduction of microorganism proliferation. © 2009 by Quintessence Publishing Co Inc.
Keywords: Comparative study; Periodontal disease/drug therapy; Periodontal disease/microbiology; Tetracycline/therapeutic use